Ilḥāḥ Maʿrifat al-ʿAlāqah al-Dalāliyyah Bayn al-Alfāẓ al-Mutarādifah - Moh Ismail (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
One of the most important fields of knowledge that contributes to understanding the Book of Allah (the Qur'an) is the study of language. Among the linguistic disciplines essential for comprehending the meanings of the Qur'an is semantics. The study of semantics has become a branch of modern linguistics that examines the meanings of words and their relationships with other meanings. Among the scholars who have studied the semantic relationships of Qur'anic vocabulary is Toshihiko Izutsu. Izutsu explains that this approach seeks to analyze Qur'anic terms and trace the history of their usage, both before the advent of Islam and after the revelation of the Qur'an, in order to clarify their intended meanings. One important approach to understanding the meaning of a word is the study of semantic synonymy. By recognizing synonymic relationships, one can better grasp the precise meaning intended within the context of a particular Qur'anic verse, thereby avoiding confusion between words that appear similar in meaning but differ in their actual usage. Accordingly, this article discusses the semantic relationships among Qur'anic vocabulary, with particular attention to synonymic relations.